Analisis Pengaruh Pengaturan Close Side Setting (CSS) Cone Crusher Terhadap Kapasitas Produksi Dalam Meningkatkan Produk Split 1-2 CM Pada Tambang Andesit PT. Koto Alam Sejahtera - Anisa Rahmi; Syamsul Bahri; Murad Murad (Journals Mining Engineering : Bina Tambang, 2018)
PT. Semen Padang has 4 units of crushing plant there are crusher II, IIIA,IIIB, and VI. Production of limestone crusher in April 2017 is 692,755 tons, while thetarget of limestone crusher production is 804,749 tons so the target of limestonecrusher production in PT. Semen Padang in April 2017 was not achieved. This iscaused of the target crusher working hours are not achieved, frequent improvementsin the crusher, and the change of usage belt conveyor lines. The purpose of thisresearch is to get the performance value of crushing plant and belt conveyor, get theproduction capacity of belt conveyor, reveal the ideal crusher working system so wecan get the ideal limestone crusher production.This research was combined between theory with field data, then we can getthe problem solving approach, and the result of data processing will be analyzed forsubsequent to be generated a recommendation.Based on the research result can be concluded. First, the performance ofcrushing plant and belt conveyor is not optimal because the work efficiency oflimestone crusher II is 26,20%, crusher IIIA is 21,54%, and crusher IIIB is 28,33%.Second, the minimum production capacity of the belt conveyor is 1,409.7 tons/hour.Third, the ideal crusher working hours is 672 hours in a month so that the productionof limestone crusher 810,992 tons in a month.